(untitled) (Research, Society and Development, 2022)
The method traditionally applied for teaching-learning in the anatomy discipline can be enhanced with the use of three-dimensional (3D) printing technology that contributes and improves the quality of learning, offering the student an extensive and replicable database with rich details. in three-dimensional format. Bioprinting also plays an important role in clinical practice, such as in the development of prostheses and the study of anatomical variations. Thus, the present work analyzed the importance of 3D printing in the teaching-learning process and evaluated its application in clinical practice. A literature review was carried out, based on studies published between 2016 and 2022 relevant to the terms (DeCS/MeSH) “3D Printing” and “Anatomy”. Regarding the applicability of bioprinting in anatomy, anatomical models can be used for educational purposes and medical training. As for clinical practice, there are several applications in medicine, among them anatomical models for preoperative planning, medical investigation, and implants. We emphasize the importance of developing new methodologies and materials from the production of models made by digital modeling processes and making this knowledge available to students and doctors, directly benefiting the population.